Per capita food expenditure in Nay Pyi Taw, Myanmar: Is there household economies of scale? - Htar, May Thet; Myint, Theingi; Htet Hnin, Chue; Aye, Htet Marlar; Nyein Aye, Yin; Moh, Moh; Soe, Thi Thi (Asia Pacific Network for Sustainable Agriculture, Food and Energy Network (SAFE Network), 2022)
This paper empirically investigates the existence of economies of scale in food consumption, the share of food expense in total household expenditure, and the determinants of per capita food expenditure in Myanmar. The study was conducted with a total of 400 respondents from Nay Pyi Taw region and the survey took place in October 2021. The results are presented into two sections. In the first section, the descriptive statistics of the variables such as the respondents’ age, household size, education and residence are reported. The household monthly income was 227.51 USD, household monthly food expenditure was 112.49 USD, household monthly per capita food expenditure was 36.69 USD, and the share of food expenditure to total household expenditure was 70.20 % on average. In the second section, the inferential statistics of the variables are reported using the Pearson’s correlation analysis and regression analysis. Significant negative relationships were found between adult-equivalent household size and per capita food expenditure, and between income and the share of food expense in total household expenditure. The negative effect of household size on per capita food expenditure indicated by the regression analysis suggested that economies of scale in food consumption existed among the study households. Policy makers therefore need to consider economies of scale when designing the poverty alleviation programs.